Utility of the Static-99 and Static-99R With Latino Sex Offenders. (December 2017) - Leguízamo, Alejandro; Lee, Seung C.; Jeglic, Elizabeth L.; Calkins, Cynthia
The predictive validity of the Static-99 measures with ethnic minorities in the United States has only recently been assessed with mixed results. We assessed the predictive validity of the Static-99 and Static-99R with a sample of Latino sex offenders ( N = 483) as well as with two subsamples (U.S.-born, including Puerto Rico, and non-U.S.-born). The overall sexual recidivism rate was very low (1.9%). Both the Static-99 measures were able to predict sexual recidivism for offenders born in the United States and Puerto Rico, but neither was effective in doing so for other Latino immigrants. Calibration analyses ( N = 303) of the Static-99R were consistent with the literature and provided support for the potential use of the measure with Latinos born in the United States and Puerto Rico. These findings and their implications are discussed as they pertain to the assessment of Latino sex offenders.